Metabolic demand of Paralympic Alpine skiing in sit-skiing athletes - Goll, M.; Wiedemann, M. S. F.; Spitzenpfeil, P. (Journal of Sports Science & Medicine, 2015)
Paralympic Alpine Skiing comprises three main categories, namely Standing, Visually Impaired and Sitting, to one of which athletes get classified depending on their individual impairment of ability. An existing sport profile of alpine skiing for able-bodied athletes facilitates the physical preparation process of Standing and Visually Impaired athletes. However, very little is known about performance determinants as well as content and structure of the physical preparation of athletes with congenital or acquired spinal cord injury competing in the Sitting class. The objective of this study was to describe the metabolic demands of Paralympic Alpine Skiing Sitting class athletes using laboratory and field measurements. The study determined maximal oxygen uptake (VO2max), maximum heart rate (HRmax) and maximal blood lactate concentration ([La-]) as well as ventilatory thresholds in laboratory testing (n = 6) as well as on-snow in Slalom (SL) carried out in a ski dome, and Giant-Slalom (GS) on a natural slope. On-snow test variables are expressed normalized to laboratory maximum values (%VO2max, %HRmax). For SL, values reached ~30% VO2max and ~60% HRmax whereas GS values were slightly higher reaching ~50% VO2max and ~75% HRmax. Lactate concentration remained close to baseline values for SL and was slightly higher at ~3 mmol·L-1 for GS. All athletes remained below their second ventilatory threshold and even skied for a long portion of runtime below their first ventilatory threshold. In general, measured metabolic values were lower than reported for able-bodied alpine skiers. However, despite the small and inhomogeneous sample covering all but one sit-skiing classes, strain of sit-skiing appears to be consistent throughout the five sit-skiing classes. Common measures of aerobic or anaerobic performance variables do not suggest further investigations in the field of metabolism for performance determinants in sit-skiing.